Obesity and Its Impact on Adverse In-Hospital Outcomes in Hospitalized Patients With COVID-19 - Keller, Karsten; Sagoschen, Ingo; Schmitt, Volker H.; Sivanathan, Visvakanth; Espinola-Klein, Christine; Lavie, Carl J.; Münzel, Thomas; Hobohm, Lukas (Frontiers in Endocrinology, 2022)
Background An increasing level of evidence suggests that obesity not only is a major risk factor for cardiovascular diseases (CVDs) but also has adverse outcomes during COVID-19 infection. Methods We used the German nationwide inpatient sample to analyze all hospitalized patients with confirmed COVID-19 diagnosis in Germany from January to December 2020 and stratified them for diagnosed obesity. Obesity was defined as body mass index ≥30 kg/m2 according to the WHO. The impact of obesity on in-hospital case fatality and adverse in-hospital events comprising major adverse cardiovascular and cerebrovascular events (MACCE), acute respiratory distress syndrome (ARDS), venous thromboembolism (VTE), and others was analyzed. Results We analyzed data of 176,137 hospitalizations of patients with confirmed COVID-19 infection; among them, 9,383 (5.3%) had an additional obesity diagnosis. Although COVID-19 patients without obesity were older (72.0 [interquartile range (IQR) 56.0/82.0] vs. 66.0 [54.0/76.0] years, p < 0.001), the CVD profile was less favorable in obese COVID-19 patients (Charlson comorbidity index 4.44 ± 3.01 vs. 4.08 ± 2.92, p < 0.001). Obesity was independently associated with increased in-hospital case fatality (OR 1.203 [95% CI 1.131–1.279], p < 0.001) and MACCE (OR 1.168 [95% CI 1.101–1.239], p < 0.001), ARDS (OR 2.605 [95% CI 2.449–2.772], p < 0.001), and VTE (OR 1.780 [95% CI 1.605–1.973], p < 0.001) and also associated with increased necessity of treatment on intensive care unit (OR 2.201 [95% CI 2.097–2.310], p < 0.001), mechanical ventilation (OR 2.277 [95% CI 2.140–2.422], p < 0.001), and extracorporeal membrane oxygenation (OR 3.485 [95% CI 3.023–4.017], p < 0.001). Conclusions Obesity independently affected case fatality, MACCE, ARDS development, VTE, and other adverse in-hospital events in patients with COVID-19 infection. Obesity should be taken into account regarding COVID-19 prevention strategies, risk stratification, and adequate healthcare planning. Maintaining a healthy weight is important not only to prevent cardiometabolic diseases but also for better individual outcomes during COVID-19 infection.